A comprehensive review on leguminous galactomannans: structural analysis, functional properties, biosynthesis process and industrial applications. Issue 2 (31st December 2021) - Sharma, Priya; Sharma, Sandhya; Ramakrishna, G.; Srivastava, Harsha; Gaikwad, Kishor
Abstract: Galactomannans are neutral hemicellulose biopolymers that strengthen the plant cell walls by interacting with cellulose in the form of storage polysaccharides. They are abundant in nature and are majorly present in the secondary walls of flowering plants. They are primarily extracted from the leguminous seed endosperms and display a wide variation at the structural and abundance level amongst different plant species. Over the last few decades, galactomannans have attracted huge attention due to their unique functional, solution and rheological properties, generally defined by their molar mass and the degree of substitution by galactosyl side chain, which differs between plants. Further, they are nontoxic, originate from renewable sources, fairly inexpensive, and are amenable to both chemical and biochemical modification. Moreover, excellent thickening, stabilizing and gelling abilities of these biopolymers have found extensive use in food, pharmaceutical, biomedical and cosmetic industries. Significant progress has been made to identify and characterize the genes responsible for biosynthesis of galactomannan along with the elucidation of controlling networks by using genetic, bioinformatics and biochemical approaches. This is the first comprehensive coverage on galactomannans which combines detailed structural and physicochemical properties as well as biology associated with the metabolism of galactomannans. It also focuses on different leguminous sources leading to various food and non-food applications of galactomannans.